A Qualitative Examination of Post-Traumatic Growth in Multiply Body Modified Adults. Issue 5 (3rd May 2020) - Keagy, Carolyn D.
ABSTRACT: This work is based on data from a qualitative research study of multiply body modified individuals in the greater San Francisco Bay Area. Participant narratives produced emergent findings of significant life stress, and traumatic events, in the lives of multiply body modified individual. The following publication provides original data regarding the domains of post-traumatic growth as expressed by multiply body modified individuals in their life narrative. Of the five domains (new paths, personal strength, appreciation, increased spirituality, and closer relationships) the most frequent that was reflected in their body modification was an increased sense of personal strength.